EVALUASI KEBIJAKAN PENANGGULANGAN BENCANA DARURAT MELALUI PROGRAM CALL CENTER U-GARUDA 112 DI KABUPATEN KUDUS - Kamila, Rulla Hasna; Warsono, Hardi; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The potential for disasters in various parts of Indonesia from year to year is very threatening to people's lives, one of which is in Kudus Regency. Kudus Regency has the potential for floods, landslides, strong winds, fires, and droughts due to low topographic conditions, heat intensity, and steep slopes. Thus, the government issued a policy in the form of the U-Garuda 112 call center program as an emergency response service when experiencing disaster and emergency events. However, its practice shows problems that it does not yet have a specific and clear local regulation on 112 services, human resources, infrastructure, and budget have not reached the target, there is a data gap that occurs with the reported data, prank calls, lack of information disclosure and does not yet have an official website. The purpose of this study is to evaluate the U-Garuda 112 call center program policy and analyze the supporting and inhibiting factors for program evaluation. This research uses Bridgman and Davis policy evaluation indicators and Muh. Mujab's supporting and inhibiting factors for program evaluation. This research uses descriptive qualitative methods through interviews, observation, and documentation. The results showed that the U-Garuda 112 program has not run well and effectively due to constraints in the quality of human resources and infrastructure, lack of role clarity, and lack of fulfillment of tasks and functions. Supporting factors for program evaluation are financial support, general and community management, apparatus dominance in policy, private involvement, and stakeholder commitment. Meanwhile, the inhibiting factors are lack of understanding of the program, miscommunication, sectoral ego, difficulty in being on time, and lack of involvement of other agencies. Recommendations that can be given are to conduct regular coordination and open communication, conduct routine maintenance on the system, conduct active and massive socialization, and improve regulations, agendas, and information disclosure.